2013
DOI: 10.1007/s00381-013-2303-5
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic carotid-cavernous fistula at the anterior ascending segment of the internal carotid artery in a pediatric patient

Abstract: It is important to keep a high degree of suspicion for CCF, especially in traumatic head injury associated with skull base fracture, since the early diagnosis and treatment may prevent potentially permanent neurological deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3,13 Traumatic fistulas, such as type A (direct) fistula, are most often due to head trauma associated with craniofacial trauma and skull base fracture. 6,7 Our patient, a 2-year-old girl, was younger than all previously reported cases (►Table 1). She presented with chemosis, proptosis caused by venous engorgement and palsy of the third cranial nerve, and orbital murmur caused by the arterial flow in the superior ophthalmic vein.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…3,13 Traumatic fistulas, such as type A (direct) fistula, are most often due to head trauma associated with craniofacial trauma and skull base fracture. 6,7 Our patient, a 2-year-old girl, was younger than all previously reported cases (►Table 1). She presented with chemosis, proptosis caused by venous engorgement and palsy of the third cranial nerve, and orbital murmur caused by the arterial flow in the superior ophthalmic vein.…”
Section: Discussionmentioning
confidence: 59%
“…Traumatic carotid-cavernous fistula (TCCF) is a very rare occurrence in the pediatric population, with a frequency of 0.2 to 0.3% after craniofacial trauma, and increasing up to 4% following skull base fractures. 3 5 6 Despite its rare occurrence, TCCF reported in children can be accompanied by drastic consequences such as intracerebral hemorrhage, de novo aneurysm formation, and irreversible vision loss or ophthalmoplegia. 6 7 Due to the high vulnerability of pediatric patients, the TCCF's neurological sequelae are associated with higher burden of visual disability and potential mortality in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the literature on posttraumatic CCF in pediatric patients aged 10 years or younger (Table 1) and found that Barburoglu et al reported two pediatric cases of CCF treated with flow diverter stents but gave no details about their age [1]. Only seven traumatic CCF cases in patients aged 10 years or younger who were treated with other methods have been reported [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Rangel-Castilla et al, 2014 [38] Retrospective [34] Case Report [12] Retrospective review between 1998 and 2011 2012 [14] Berker et al, 2012 [2] Case 2011 [44] Case Report [22] Case Report 2009 [39] Case report 2008 [3] Case report [5] Case report 2007 [26] Case series…”
Section: Patient Outcome Commentsmentioning
confidence: 99%